2010
DOI: 10.1037/a0018260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of obsessive-compulsive symptom dimensions: Development and evaluation of the Dimensional Obsessive-Compulsive Scale.

Abstract: Although several measures of obsessive-compulsive (OC) symptoms exist, most are limited in that they are not consistent with the most recent empirical findings on the nature and dimensional structure of obsessions and compulsions. In the present research, the authors developed and evaluated a measure called the Dimensional Obsessive-Compulsive Scale (DOCS) to address limitations of existing OC symptom measures. The DOCS is a 20-item measure that assesses the four dimensions of OC symptoms most reliably replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
471
4
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(531 citation statements)
references
References 64 publications
17
471
4
15
Order By: Relevance
“…The DOCS has been shown to be a valid and reliable assessment of OCD symptom dimension severity across clinical populations (Abramowitz et al 2010). The DOCS has excellent internal consistency (Cronbach's α = 0.90; Abramowitz et al 2010). …”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DOCS has been shown to be a valid and reliable assessment of OCD symptom dimension severity across clinical populations (Abramowitz et al 2010). The DOCS has excellent internal consistency (Cronbach's α = 0.90; Abramowitz et al 2010). …”
Section: Participantsmentioning
confidence: 99%
“…Abramowitz et al 2010) is a 20-item self-report measure that assesses the severity of four OCD symptom dimensions (contamination, responsibility for harm and mistakes, symmetry/ordering, and unacceptable thoughts) on a scale of 0 to 4 (total scores ranges from 0 to 80) with the clinical cut-off score of 21 for OCD. The DOCS has been shown to be a valid and reliable assessment of OCD symptom dimension severity across clinical populations (Abramowitz et al 2010). The DOCS has excellent internal consistency (Cronbach's α = 0.90; Abramowitz et al 2010).…”
Section: Participantsmentioning
confidence: 99%
“…As Gönner et al (2010) Another major problem with VOCI and other non-dimensional measures as Abramowitz et al (2010) indicate is that "these measures have a number of important drawbacks that detract from their ability to provide a time efficient, empirically consistent, and conceptually clear assessment of OC symptom severity" (p. 181). Based on such an evaluation they have introduced Dimensional Obsessive-Compulsive Scale.…”
Section: Discussionmentioning
confidence: 99%
“…Factor analytic studies have consistently identified five subgroups of symptoms: (a) contamination obsessions and washing/cleaning compulsions; (b) obsessions about responsibility for causing harm or making mistakes and checking compulsions; (c) obsessions about order and symmetry and ordering/arranging compulsions; (d) repugnant obsessional thoughts concerning sex, religion and violence along with mental compulsive rituals and other covert neutralizing strategies, and (e) hoarding (Abramowitz et al, 2010;Leckman et al,1997;Mataix-Cols et al, 2005). Some suggest that hoarding should be considered a distinct disorder from OCD, with its own diagnostic criteria in the next edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) (Pertusa et al, 2010;Leckman et al, 2010).…”
Section: Subtypesmentioning
confidence: 99%